Daya Hambat Kayu Manis (Cinnamomum burmanni) terhadap Pertumbuhan Bakteri Kultur Darah Widal Positif Anggota Familia Enterobacteriaceae: The Inhibition of Cinnamom on Growth of Bacterium on the Positive Widal Blood Culture of Enterobateriaceae Family Member - Rahmah, Windya Nazmatur (Borneo Journal of Medical Laboratory Technology, 2021)
Cinnamon has a high activity of antibacterial. Still, the antibacterial effect toward the bacteria on the positive Widal blood culture of Enterobacteriaceae family members was not clear yet. This research aimed to find out the inhibition of cinnamon on the growth of bacterium on the positive Widal blood culture of Enterobacteriaceae family members. The method used in the research was experimental research which was using the draw well method and using Salmonella typhi, Escherichia coli, Klebsiella pneumonia, Serratia marcescens, and Enterobacter cloacae bacteria samples. Cinnamon as a test solution with a 2%, 4%, 6%, 8% and 10% concentrate. The research result was showed the inhibiting zone was able to form on the Nutrient Agar Plate (NAP) on growth of the Enterobacteriaceae, 10% concentrate that high sensitive showed to S. typhi, Ser. marcescens, E. cloacae, E.coli, and Kleb. pneumonia squent was 12 mm, 11 mm, 11 mm, 10 mm, and 8,5 mm. At the same time, 8%, 6%, 4%, and 2% concentrate of cinnamon could not perform inhibition zone 100 µl of the test solution with chloramphenicol as a positive control.